Microbial photoelectrosynthesis: Feeding purple phototrophic bacteria electricity to produce bacterial biomass. Issue 3 (19th December 2022) - Manchon, Carlos; Muniesa‐Merino, Fernando; Llorente, María; Esteve‐Núñez, Abraham
Abstract: Purple phototrophic bacteria are one of the main actors in chemolithotrophic carbon fixation and, therefore, fundamental in the biogeochemical cycle. These microbes are capable of using insoluble electron donors such as ferrous minerals or even carbon‐based electrodes. Carbon fixation through extracellular electron uptake places purple phototrophic bacteria in the field of microbial electrosynthesis as key carbon capturing microorganisms. In this work we demonstrate biomass production dominated by purple phototrophic bacteria with a cathode (−0.6 V vs. Ag/AgCl) as electron donor. In addition, we compared the growth and microbial population structure with ferrous iron as the electron donor. We detect interaction between the cathode and the consortium showing a midpoint potential of 0.05 V (vs. Ag/AgCl). Microbial community analyses revealed different microbial communities depending on the electron donor, indicating different metabolic interactions. Electrochemical measurements together with population analyses point to Rhodopseudomonas genus as the key genus in the extracellular electron uptake. Furthermore, the genera Azospira and Azospirillum could play a role in the photoelectrotrophic consortium. Abstract : Carbon fixation through extracellular electron uptake places purple phototrophic bacteria in the field of microbial electrosynthesis as key carbon capturing microorganisms. In this work we demonstrate biomass production dominated by purple phototrophic bacteria from Rhodopseudomonas genus with a cathode (−0.6 V vs. Ag/AgCl) as electron donor.